An examination of activism and 'political listening' during the year of student protest at the University of Cape Town from 9 March 2015 to 9 March 2016 - Mufamadi, Azwihangwisi Eugene (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
This study sets out to examine democratic participation in South Africa and the role that 'political listening' could play in making participation more equitable. It considers protest action on a South African university campus, which at times not only resulted in significant and swift concessions from the university leadership but also sparked national political action which got an equally swift response from the South African government. It considers the social movement, the RhodesMustFall movement (RMF), as one way in which students can organise themselves to get a better hearing from the University of Cape Town (UCT) management in their attempt to make a meaningful contribution to the university's micro democracy. This study examines whether the interaction between the UCT management and RMF could be considered 'political listening', and the possible role of the Cape Times newspaper within this context of participation. Using data gathered through interviews, written communications, observation and newspaper articles, the study shows that in all of the interactions between RMF and the UCT management, both groups were seldom willing to forego their power to engage in genuine listening. Instead, the two parties guessed at what power the other party might have and acted to reduce that power. It is in this context of guessing at and figuring what power the other party has that listening occurs. Furthermore, the study shows that during the RMF protest, the UCT management viewed their responsibility for the institution mainly through the lens of Private Property Law which framed protest as something to be dealt with by restoring law and order. The study also details the role of the Cape Times newspaper in the interactions between RMF and the UCT management and considers if this role could be political listening. The study is exploratory and demonstrates how political listening could work more optimally in real-life instances.
Keywords: Student movements -- South Africa -- Cape Town; Democracy -- South Africa; Listening -- Political aspects; Journalistic ethics; Journalism -- Political aspects; Communication in social action -- South Africa -- Cape Town; University of Cape Town; Cape Times Ltd.